CORRELATION STUDY BETWEEN WORK-FAMILY CONFLICT AND WORK DISCIPLINE WITH EMPLOYEE PERFORMANCE (A SURVEY BINAPENTA DIRECTORATE) - Chintya Dewi (Universitas Trisakti, 2011)
The background of this research is to analyze the work family conflict and work discipline in relation with performance employee of Direktorat Binapenta at Kementerian Tenaga kerja and Transmigrasi RI. There are some cases on employee performance that found often. First, the conflicts that occur in organizations and employees performance. Second, employees’ lack of discipline which resulted in a delayed performance. Third, employees with above average workfamily conflict and dicipline with a slow employee performance track. The objective(s) of this research was formulated as: 1) Is there any correlation between work-family conflict and employee perfomance of Dirjen Binapenta at Kemenakertrans RI, 2) Is there any correlation between work dicipline and employee perfomance of Dirjen Binapenta at Kemenakertrans RI, 3) Is there any correlation between work-family conflict and work dicipline jointly with employee perfomance of Dirjen Binapenta at Kemenakertrans RI. Data analyze used in this research was primary data by using a simple random sampling to collect data. Analysis data method in this research is using correlation method. Respondent on this research are the employees of Dirjen Binapenta Kemenakertrans RI. The result of this research concludes that the first hypothesis which has been done to identify; Ho1 can be rejected and accept Ha1 by considering the value of pearson correlation in level 0,561 and the value significant in level 0,000; for which it is similar to the terms that if the value of significant is still under p < 0,005 and the value significant p = 0,000; value b = 0,361 and the value of t = 6,356; on second hypothesis, it identified that Ho2 can be rejected and accept Ha2 by considering the value of pearson correlation in level 0,615 and the value significant in level 0,000; for which it is similir to the terms that if the value of significant p < 0,05 and the value significant p = 0,000; value b = 0,547 and the value of t = 7,313; on the third hypothesis, it succeed to rejected Ho3 and accept Ha3, by obtaining the value multiple correlation in level 0,660 and Anova significant value in level 0,000; for which it is still under p < 0,005; and the value of significant work discipline p = 0,000; value beta 0,387. From the result Anova, F calculate value 33,539 larger ones from F table, indicates that work-family conflict and work dicipline jointly having relationship with employee performance of Dirjen Binapenta at Kemenakertrans RI. It means positive work-family conflict and work dicipline cause more higher employee perfomance. Thereby, needs existence for the lack work-family conflict and positive work dicipline from employee, causing can improve high spirit in working maximizing potency employee in increasing employee performance.